Candida genus - Virulence factores, Epidemiology, Candidiasis and Resistance mechanisms (Research, Society and Development, 2021)
The genus Candida is found symbiotically living in the microbiota of the reproductive and gastrointestinal mucosa of 50-70% of healthy individuals, under certain conditions these microorganisms can become pathogenic, to the point of becoming the third cause of septicemia worldwide. They can cause superficial infections, affecting mucous membranes and skin, as well as invasive infections, in organs and deep tissues such as intestines, lungs and blood. The most isolated species in infections caused by the genus is Candida albicans, however the isolation of species of Candida non-albicans, such as C. glabrata, C. krusei, C. tropicalis and C. parapsilosis is increasingly recurrent. In addition, C. albicans and C. non-albicans species have been increasingly reported due to the emergence of resistance to antifungal agents for clinical use, making it difficult to treat infections caused by these strains. This work aimed to gather updated information about the genus Candida on virulence factors, epidemiology, candidiasis, treatments and resistance mechanisms.